Pengaruh Teknik Grafting dan Okulasi terhadap Pertumbuhan dan Keberhasilan Perbanyakan Tanaman Alpukat (Persea americana) - Ira Rahmawati; Hilwa Kamilatunnuha; Luthfi Hana Fadiah; Muhammad Mubiar Ramadana; Muhammad Rafi Fauzan; Ita Fitriyah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
This study aims to evaluate the effect of grafting and budding techniques on the growth and success of avocado (Persea americana) plant propagation. Grafting and budding techniques are vegetative methods commonly used in horticultural plant propagation to maintain the genetic quality of the parent plant. The study was conducted using avocado plants with grafting and budding techniques on the rootstock. The parameters observed included the level of success of unification (compatibility rate), shoot growth rate, survival percentage, and growth in stem diameter and plant height during a certain period. The results showed that the grafting technique provided a higher success rate than the budding technique on certain varieties, with a survival percentage reaching 85%. However, the budding technique showed advantages in the parameter of shoot growth rate, especially on varieties with specific or better environmental adaptation. This study shows that choosing the right propagation technique, depending on the characteristics of the variety and environmental conditions, is a key factor in supporting the success of avocado plant propagation. These findings are expected to be a reference for farmers and researchers in optimizing the production of high-quality avocado seedlings.